Distributed Leadership Practices by principals working in Type 2 and Type 3 schools in the Colombo District, Sri Lanka - Kumari, H.M.L. (International Journal of Latest Technology in Engineering, Management & Applied Science, 2022)
This study examined on the distributed leadership practices by principals working in type 2 and type 3 schools in Colombo District, Sri Lanka. The objectives of this study were to identify how principals and teachers understand the concept of distributed leadership; how distributed leadership practices enhance teaching and learning; and what challenges principals and teachers face when devolving and practicing leadership responsibilities in their schools. Using random sampling method altogether 08 schools, 08 principals, 08 sectional heads and 150 teachers were selected for the study. Both questionnaires and semi-structured interviews were used to gather necessary data and information. The findings revealed that all the principals in the type 2 and type 3 schools fully understood the concept of distributed leadership. However, a significant number of teachers in both types schools have not understood the concept of distributed leadership. The study further revealed that the distributed leadership practices in both types schools did not contribute to enhance the quality of instruction to a satisfactory level. It was further revealed from this study that a significant number of teachers and principals in both types schools face number of challenges when practicing distributed leadership roles due to the major challenge of retention of experienced teachers as they trying to get transfers to the so called 1AB schools, insufficient resources and unsatisfactory collaborative working culture.
Keywords: Leadership; Distributed Leadership; Colombo District; Type 2 Schools; Type 3 Schools